Assessment of human-structure interaction on a lively lightweight GFRP footbridge. (15th November 2019) - Ahmadi, Ehsan; Caprani, Colin; Živanović, Stana; Heidarpour, Amin
Highlights: Human-structure interaction (HSI) is not presently considered in many design guidelines. Structural use of lightweight materials such as glass fibre-reinforced polymers is increasing. The effect of HSI is explored for a full-scale laboratory footbridge through extensive testing. Traditional moving force models are found to poorly represent the responses. The bridge vibration is found to strongly influence imparted walking forces. Abstract: Human activities and occupancy can induce excessive structural vibrations. Human-structure interaction (HSI) can significantly affect responses. However, this phenomenon is not accounted for in many design guidelines due to lack of experimental studies. Concurrently, there is increasing application of lightweight high-strength materials such as glass fibre reinforced polymer (GFRP). The vibration sensitivity of such structures is not yet well known, despite the expectation that it could be important due to high human-to-structure mass ratio. This paper examines the effect of HSI on the vibration response prediction of a lively lightweight GFRP footbridge, and it compares the results to those from a heavy concrete-composite footbridge. An extensive ensemble of test trials was conducted, accompanied by a survey on vibration perception by the walkers. The influence of HSI on the lightweight bridge vibration response is quantified. It is found that the non-interacting moving force models produce poor predictions, especially for the GFRP bridge. It is also found that vibration of the bridge had a strong influence on walking force, and to a lesser extent on the dynamics of the human-structure system. Finally, it is found that a response factor of about 2 is appropriate for determining the vibration tolerance level by walkers.